Controlled-release of fluazinam from biodegradable PLGA-based microspheres. Issue 10 (3rd October 2019) - Wang, Qi; Shen, Mengfei; Li, Wenjing; Li, Wanwan; Zhang, Fang
Abstract: Pesticides are biological or chemical substances used to manage pests and diseases. Encapsulation of pesticides in biodegradable carriers creates a slow-release system that can improve water dispersibility and prolong residual activity. We prepared two kinds of poly (lactic-co-glycolic acid)(PLGA) nanoparticles (NPs) with polyvinyl alcohol (PVA) and sodium dodecyl sulfate (SDS) surfactants. These were used to encapsulate the fungicide fluazinam (Flu) against Rhizoctonia solani using the Shirasu Porous Glass (SPG) membrane emulsification method. Both nanoparticles had uniform spherical shapes with average diameters of 314.13 nm (SDS) and 612.80 nm (PVA). The slow-release microspheres had excellent sustained-release properties, resistance to UV degradation, storage stability, leaf surface coverage and antifungal efficacy compared to the commercial formulation.